2015
DOI: 10.1542/peds.2014-2291
|View full text |Cite
|
Sign up to set email alerts
|

First Pertussis Vaccine Dose and Prevention of Infant Mortality

Abstract: BACKGROUND: American infants are at highest risk of severe pertussis and death. We investigated the role of $1 pertussis vaccinations in preventing pertussis-related deaths and risk markers for death among infants aged ,42 days. METHODS:We analyzed characteristics of fatal and nonfatal infant pertussis cases reported nationally during 1991-2008. Infants were categorized into 2 age groups on the basis of eligibility to receive a first pertussis vaccine dose at age 6 weeks; dose 1 was considered valid if given $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 43 publications
1
28
0
2
Order By: Relevance
“…A recent US study provides detailed age distribution by week of age for 258 deaths identified through national case surveillance data rather than death certificates between 1991 and 2008 [29]. In the prevaccine period, 67% of deaths occurred by 12 months of age, but <5% were identified in the first month of life and around 15% by 2 months [24], in contrast to the US experience in 1991–2008, where almost 50% of deaths had occurred by age 1 month and 85% by 2 months [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent US study provides detailed age distribution by week of age for 258 deaths identified through national case surveillance data rather than death certificates between 1991 and 2008 [29]. In the prevaccine period, 67% of deaths occurred by 12 months of age, but <5% were identified in the first month of life and around 15% by 2 months [24], in contrast to the US experience in 1991–2008, where almost 50% of deaths had occurred by age 1 month and 85% by 2 months [29].…”
Section: Resultsmentioning
confidence: 99%
“…In the prevaccine period, 67% of deaths occurred by 12 months of age, but <5% were identified in the first month of life and around 15% by 2 months [24], in contrast to the US experience in 1991–2008, where almost 50% of deaths had occurred by age 1 month and 85% by 2 months [29]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…81 Another Australian study, also using the screening method to investigate VE of acellular vaccines against laboratory-confirmed notifications, found VE point estimates to be between 78.2% to 91.7% for children aged one to less than four years (three vaccine doses), between 64.7% and 87.4% for children aged five to less than eight years (four doses), and between 43.3% and 78.1% for children aged eight to less than 12 years (five doses). 82 Infant pertussis vaccination has been demonstrated to reduce the rate of hospitalisation, even after a single dose, [83][84][85][86] however to date, few studies have specifically assessed the effectiveness of acellular pertussis vaccines against severe infection. 82,85,87,88 Rendi-Wagner et al (2006), using the screening method, estimated that the VE for preventing hospitalisation in children aged younger than 15 years, after 3 doses, was 79%…”
Section: Vaccinesmentioning
confidence: 99%
“…4,21 The primary aim of pertussis immunisation is to protect young infants against severe Despite the well-established pertussis immunisation programs in Australia and overseas, infants younger than six months of age continue to be at highest risk of severe outcomes. 10,86,89,[103][104][105][106] In the future, new pertussis vaccines may be able to provide earlier and longer lasting protection by utilising live attenuated B. pertussis strains, novel soluble or micro-particle vaccine formulations, improved adjuvants, or mucosal delivery, [107][108][109] however as these novel vaccines may still be many years away, other strategies need to be considered to protect young infants. 10,61,103,105 The "cocoon" strategy, which attempts to protect newborn infants by immunising their close contacts, such as parents and other caregivers, has been proposed as a possible solution.…”
Section: Immunisation Strategies and Coveragementioning
confidence: 99%